Front Cover: Tank‐Circuit Assisted Coupling Method for Sympathetic Laser Cooling (Adv. Quantum Technol. 7/2021). Issue 7 (11th July 2021) - Tu, Bingsheng; Hahne, Felix; Arapoglou, Ioanna; Egl, Alexander; Heiße, Fabian; Höcker, Martin; König, Charlotte; Morgner, Jonathan; Sailer, Tim; Weigel, Andreas; Wolf, Robert; Sturm, Sven
Abstract : In article number 2100029, Bingsheng Tu and co‐workers present a novel scheme that allows to efficiently cool arbitrary ions by coupling them to a directly laser cooled ion in a separate Penning trap. The authors' results demonstrate how a common tank circuit can drastically enhance the coupling, resulting in the expected avoided‐crossing behavior of the two ions. This technique holds promise to enable millikelvin cooling of arbitrary ions in Penning traps.